Material Adaptation in the Classroom and the use of Typhlotechnology as Teachers of Students with Visual Impairment Students’ Perspective (London Journal of Research In Humanities and Social Sciences, 2024)
Technologies have been a fundamental part of education for several decades since, through their use, all students can access information more easily and remotely. However, it is not until recent years that it has been latently noticed how the attention of educators and researchers has been redirected towards students with visual impairment or other special needs in an attempt to promote their inclusion in today’s classrooms. It should be noted that the adaptation of material in the classroom and the use of typhlotechnology as teachers of students with visual impairment has not been studied much from the perspective of the students; hence the objective of this study. The data analysis was collected through the use of interviews that provided first-hand information from students with visual impairment in relation to the knowledge that their teachers have -or not- about typhlotechnology and the adaptation of materials to cover their curriculum. The data analysis was carried out with the coding of students’ responses and with the identification of topics based on the research questions. Consequently, the study indicates that students with visual impairment consider it important that their teachers are aware of the technologies used by the aforementioned to adapt the materials depending on their educational needs.
Keywords: trascendentperception; immanentperception; cognitive equilibrium; Community.; resources; Megalithism; reuse; multitemporality; Typhlotechnology; material adaptation; visual impairment